The Empirical Research on Online Software Assisted Sketching Instruction - Huang, Lian (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study evaluates the effectiveness of the online education software Meishubao in blended sketching instruction, focusing on its impact on high school students’ exam-oriented core sketching abilities. Research design, data and methodology: Using a quasi-experimental design, 72 high school art students were randomly assigned to an experimental group (Meishubao-assisted blended teaching) or a control group (traditional face-to-face instruction) for an eight-week intervention. Students were pre- and post-tested on composition, perspective, spatial experience, richness of detail, and aesthetic sensitivity, based on Sichuan Province Art Joint Examination criteria. Independent-samples t-tests were conducted in Jamovi. Results: The experimental group demonstrated significantly greater post-test gains in composition, perspective, spatial experience, and richness of detail than the control group, with no significant difference in aesthetic sensitivity. Conclusions: Meishubao addresses limitations of traditional instruction—such as monotonous skill drills and insufficient individualized guidance—by offering real-time feedback and personalized learning paths, thereby significantly improving sketching outcomes in blended settings. Implications and future directions: The findings provide empirical support for the digital transformation of art education and suggest that Meishubao-enabled blended learning is a promising exam preparation strategy. Future studies should expand sample size and duration and explore AI-optimized interactive modes. To further advance technology-supported art education.